Epigenetic Control of Autophagy Related Genes Transcription in Pulpitis via JMJD3 - Yin, Bei; Ma, Qingge; Zhao, Lingyi; Song, Chenghao; Wang, Chenglin; Yu, Fanyuan; Shi, Yu; Ye, Ling (Frontiers in Cell and Developmental Biology, 2021)
Autophagy is an intracellular self-cannibalization process delivering cytoplasmic components to lysosomes for digestion. Autophagy has been reported to be involved in pulpitis, but the regulation of autophagy during pulpitis progression is largely unknown. To figure out the epigenetic regulation of autophagy during pulpitis, we screened several groups of histone methyltransferases and demethylases in response to TNFα treatment. It was found JMJD3, a histone demethylase reducing di- and tri-methylation of H3K27, regulated the expression of several key autophagy genes via demethylation of H3K27me3 at the gene promoters. Our study highlighted the epigenetic regulation of autophagy genes during pulpitis, which will potentially provide a novel therapeutic strategy.